FACTORS OF HAPPINESS AT WORKPLACE – A REVIEW OF STUDIES FROM 1999 TO 2021. (International Journal of Food and Nutritional Sciences, 2022)
The role of happiness in our life is a well-known fact. Happy employees are also very productive and less prone to accidents, burnout and absenteeism. However, what is factors of happiness at the workplace are lesser known. Hence, the present paper is devoted to finding out the various factors of happiness in the workplace. The author reviews the research papers published from 1999 to 2021 in the relevant field.